Life of the party [videorecording (DVD)] - Falcone, Ben, 1973-; Falcone, Ben, 1973-; Falcone, Ben, 1973-; Falcone, Ben, 1973-; McCarthy, Melissa, 1969-; McCarthy, Melissa, 1969-; McCarthy, Melissa, 1969-; Walsh, Matt, 1964-; Gordon, Molly, 1994- (Warner Bros. Entertainment, 2018)
After her husband leaves her, a homemaker decides to return to college and ends up in the same school and class as her daughter.